The Effectiveness of Flipped Classroom in Teaching Grammar of EFL Students - Saidah, Saidah (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this research was to investigate the effect of using the flipped classroom strategy to students’ grammar mastery. To apply the strategy the researcher selected some videos from YouTube which was being studied by the students. These videos were chosen based on the students’ text book. Then, she uploaded those videos on group WhatsApp of experimental group before class. The videos were watched by the experimental group at home before class in order to give them basic knowledge of the material used by the students in the class. The class meeting is used to check the students understanding of the materials by quiz. The students also were asked to complete tasks in groups. Meanwhile, the students from the control group were taught by grammar translation method. It was obvious from the post-test analysis that applying the flipped classroom strategy was able to enhance the students’ grammar performances, as the t score is higher than t table, which means that there was significant different between control and experimental group which were taught by using flipped classroom.